Biodiversity and Abundance of Angiosperms and Environmental Resilience in the Tidal Range of Yuanjiang Dry–Hot Valley, Southwestern China - Fengchun Yang; Qiong He; Huaping Huang; Yanmei Cui; Jianyong Gou; Chaya Sarathchandra; Kritana Prueksakorn; Kiyota Hashimoto; Li Liu (Diversity)
Yuanjiang dry–hot valley is located in the southwest of mainland China. It is a sparsely vegetated area with a fragile arid ecosystem. Although the valley previously had forest cover, it has become a tropical montane savannah in recent decades. Mechanisms controlling plant species distribution in such dry–hot valleys are unclear. Clarifying this will be beneficial to sustainable ecosystem management in dry–hot valleys. This study explored the relationship between diversity patterns of plant species and their environments in the lowland of this dry–hot valley. To achieve this, transects and plots were arranged along the river channel. Alpha and beta diversity indices were calculated to quantify biodiversity changes between species and environments. Estimated species, rarity, and abundance indices were also utilized to examine the correlation among species, their population size, and their environment: Species_estimated (expected number of species in t pooled plots), Singletons (the number of species with only one individual in t pooled plots), Uniques (the number of species living in one plot in t pooled plots), ACE (species richness estimator with coverage-based abundance), ICE (species richness estimator with coverage-based incidence), and Chao2 (species richness estimator extrapolated from Singletons). Fifty years of meteorological records, including temperature and precipitation, were utilized as climate variables. The results indicated the following findings: (1) alpha diversity was higher closer to the river, whereas the beta diversity was higher towards the lower sections of the river (Bray–Curtis < 0.5), but this trend was reversed in the perpendicular transects; (2) total phosphorous (TP) and total potassium (TK) were higher on flatter ground, tending to be associated with raised nitrogen (TN) and organic matter (OM); (3) soil nutrients were higher towards the lower sections of the river, corresponding to an increased number of species; (4) water supply determined plant distribution, with soil condition determining water retention; (5) the estimated species and their rarity and abundance indices were associated with proximity to the river, indicating heterogeneity of habitats and soil condition; and (6) fern species could be used as indicators representing the xeric environment of Yuanjiang dry–hot valley. Plant cover was reduced at low altitudes, with high temperatures and a low water supply. These results draw attention to the need for specific policy formation to protect the microhabitats and manage the environment of the Yuanjiang valley.